1998
DOI: 10.1038/sj.jhh.1000564
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four hour ambulatory blood pressure: a sample from a normal British population

Abstract: The aims of this study were to determine 24 h blood step-wise regression with age, gender, weight and height showed age to be the best predictor of variation pressure (BP) levels in a sample taken from a normal British population, and to investigate factors contribuin office BP and awake and asleep diastolic BP. However, age accounted for only a small amount of the variting to variation within the sample. Two hundred and eighty-two Caucasian subjects, with no known hyperation and did not contribute towards the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 5 publications
0
17
2
Order By: Relevance
“…In the HARVEST study, among never-treated borderline to mild young hypertensives (n=1062), nocturnal BP nondipping was present in 31% 18. One study of a British population published in 1998 found that among 265 healthy, normotensive volunteers who underwent office and ambulatory BP measurements, 17% were nondippers 19. Compared to the participants in our study, those in the British study were slightly older with a mean age of 39 years.…”
Section: Discussioncontrasting
confidence: 54%
“…In the HARVEST study, among never-treated borderline to mild young hypertensives (n=1062), nocturnal BP nondipping was present in 31% 18. One study of a British population published in 1998 found that among 265 healthy, normotensive volunteers who underwent office and ambulatory BP measurements, 17% were nondippers 19. Compared to the participants in our study, those in the British study were slightly older with a mean age of 39 years.…”
Section: Discussioncontrasting
confidence: 54%
“…It has been consistently shown that ambulatory BP measurements are more powerful to predict LVH than is office BP. 26,27 However, multiple subgroup analyses with and without adjustment for BP levels failed to show in the present study an association between the GNB3 poly- …”
Section: Discussioncontrasting
confidence: 38%
“…The methods of OBP and awake ABP measurements in the selected studies are shown in Supplemental Table 1 (S1). In the meta-analysis of the 23 studies of adults (N=10249) 7,15,16,2025,28,29,3138,4042,44 , office systolic/diastolic BP [mean (95 % confidence intervals)] was 1.8 (1.8–1.9)/1.9 (1.8–2.0) mmHg higher than awake ABP (both P<0.001), but in the parallel analysis of the 5 studies of children and youth (N=1829) 26,27,30,39,43 , awake ABP was 8.4 (8.2–8.5)/7.0 (6.9–7.1) mmHg higher than office BP (both P<0.001).…”
Section: Resultsmentioning
confidence: 99%